Monitoramento e desempenho da vegetação no conforto térmico em espaços livres urbanos : o caso das praças de Maringá/PR - Lima, Diana Carla Rodrigues (2009)
The vegetation exerts several effects in the urban microclimate. Today its use is one of the strategies recommended for the ambient project with intention to reduce the energy consumption, to minimize the effect of the urban climate and to provide thermal comfort to the man. Therefore it is component of great importance to the urban space and has awakened the attention not only of researchers, but also of all the population, a time that its presence minimizes the impacts caused for the disordered growth of the city. The present work has as objective to study the influence of the present vegetation in the urban open spaces in the thermal comfort. As case study, two squares of the city of Maringá-PR had been chosen. These squares be situated in the center of the city and they have great dynamism. The characteristics of both are diverse in relation to the density of the vegetation and types of pavement; however, both are found in densely built-up areas and assume similar topographical conditions. The methodology is based on the climatic variable measurement in each square and the application of questionnaires for thermal comfort evaluation of the users. The collection of data was carried through during two consecutive days in situations of autumn, winter, spring and summer, in days of clearly sky. This work is justified for the current lack of attention excused to the squares and for the fact of that these, as public space of leisure more accessible to the population, must provide conditions of well-being for who frequent them. These conditions are expressed through the presence of vegetation that is an important condition to the thermal comfort. The results of this research demonstrate that a more pleasant urban thermal environment formation is directly associated with the presence of the vegetation.